Sterol Transport Protein ORP6 Regulates Astrocytic Cholesterol Metabolism and Brain Aβ Deposition - Vijithakumar, Viyashini (Université d'Ottawa / University of Ottawa, 2023)
The mammalian brain is the most cholesterol-rich organ of the body, requiring in situ de novo cholesterol synthesis to maintain its cholesterol requirement. Defects in brain cholesterol homeostasis are implicated in cognitive deficits related to aging and in neurodegenerative diseases such as Alzheimer's Disease (AD). Oxysterol-binding protein (OSBP) - related proteins are highly conserved cytosolic proteins that coordinate lipid homeostasis by regulating cell signaling, inter-organelle membrane contact sites and non-vesicular transport of cholesterol. Previously, ORP6, a poorly characterized member of this family, was found to be part of complex transcriptional cascade coordinated by SBREP2 and emerged as a novel regulator of intracellular cholesterol trafficking in hepatocytes and macrophages. Yet how ORP6 regulates these pathways and its function in the brain where it is most highly expressed is unknown. Here, we show that ORP6 is highly expressed in the brain, where it exhibits spatial and cell-type specific expression. ORP6 expression is enriched in the hippocampus and caudal-putamen brain regions, specifically within neurons and astrocytes. ORP6 knockdown in astrocytes altered the expression of cholesterol biosynthesis, cholesterol efflux and cholesterol esterification genes, resulting in the accumulation of esterified cholesterol within cytoplasmic lipid droplets and reduced cholesterol efflux highlighting a role for ORP6 in astrocytic cholesterol metabolism. We also present in this thesis, the newly generated second viable ORP family member knockout mouse. ORP6 ablation in mice results in the dysregulation of brain and whole-body lipid homeostasis, increased Aβ deposition in the brain and neuroanatomical alterations. Together, our findings highlight a critical role for cholesterol trafficking proteins in brain cholesterol homeostasis and identify ORP6 as a potential novel target for AD.
Keywords: Oxysterol binding proteins related proteins; cholesterol transport; lipid homeostasis; intracellular trafficking; Alzheimer's Disease; astrocytic cholesterol metabolism; cholesterol homeostasis